2014
DOI: 10.1371/journal.pone.0100506
|View full text |Cite
|
Sign up to set email alerts
|

Whole Body Vibration Improves Cognition in Healthy Young Adults

Abstract: This study investigated the acute effects of passive whole body vibration (WBV) on executive functions in healthy young adults. Participants (112 females, 21 males; age: 20.5±2.2 years) underwent six passive WBV sessions (frequency 30 Hz, amplitude approximately 0.5 mm) and six non-vibration control sessions of two minutes each while sitting on a chair mounted on a vibrating platform. A passive WBV session was alternated with a control session. Directly after each session, performance on the Stroop Color-Block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 21 publications
7
67
1
Order By: Relevance
“…WBV is known to stimulate muscle activity (Bosco et al, 1999;Burke and Schiller, 1976), and the current findings of the Balance beam with improved motor performance after WBV are therefore in full support of these observations. The improved attention in the object recognition task corroborates the found improvements in attention in humans (Fuermaier et al, 2014 a,b ; Regterschot et al, 2014, den Heijer et al, 2015.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…WBV is known to stimulate muscle activity (Bosco et al, 1999;Burke and Schiller, 1976), and the current findings of the Balance beam with improved motor performance after WBV are therefore in full support of these observations. The improved attention in the object recognition task corroborates the found improvements in attention in humans (Fuermaier et al, 2014 a,b ; Regterschot et al, 2014, den Heijer et al, 2015.…”
Section: Discussionsupporting
confidence: 84%
“…It is assumed that WBV induces sensory stimulation in cortical brain regions through the activation of skin and muscle receptors responding to the vibration. A series of studies in humans showed that two minutes of WBV applied via a chair mounted on a platform improved attention/cognitive interference in healthy (young) adults and adults with Attention Deficit Hyperactivity Disorder (ADHD) (Fuermaier et al, 2014a;Regterschot et al, 2014). Moreover, it was found that repeated WBV treatment (three times three minutes) improved cognitive interference in healthy children (den Heijer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This kind of exercise improves the strength of the muscle [35, 56, 78, 79], bone density [35, 65], cardiovascular parameters [63, 64], body balance [28], flexibility [46, 52, 54, 55, 7986], and cognition [42, 43] and is a promising treatment method for patients with acute unstable inversion ankle sprains [87]. Some of these improvements might be useful to patients with metabolic syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies reported increased muscle strength, mobility, balance and lower blood pressure after WBV [9][10][11][12]. Moreover, WBV was found to improve attention and inhibition, both acute (in schoolchildren, young adults (with ADHD)) as well as after 5 weeks (in older adults) [13][14][15][16]. Based on these findings it is thought that both TMSim and WBV will lead to a diffuse activation of different brain areas, but that the combination of TMSim + WBV will elicit the strongest effects [17].…”
Section: Introductionmentioning
confidence: 99%